Putusan Mahkmah Konstitusi tentang Upah Layak: Harapan Baru bagi Dunia Ketenagakerjaan Indonesia - Irayadi, Muhamad (HUMANIORUM, 2024)
The Constitutional Court's ruling on living wages is an important milestone in Indonesian labour policy. This study analyses the effectiveness of the implementation of the ruling and the factors that influence its implementation. Despite providing new hope for workers, the implementation still faces challenges, such as different interpretations of living wages between the government, employers, and labour unions, as well as economic instability that affects companies' ability to fulfil wage requirements. In addition, weak supervision and law enforcement lead to companies' non-compliance with labour policies. To improve the effectiveness of implementation, a collaborative approach between the government, employers and trade unions through constructive dialogue and policies that are adaptive to economic conditions is needed. This research recommends strengthening cooperation between stakeholders, increasing public awareness of labour rights, and stricter law enforcement to ensure effective and sustainable implementation of living wages.